Effect of Emulsification Process Conditions on the Properties of Water-in-Bitumen Emulsion - Alade, Lekan; Yuichi, Sugai; Sasaki, Kyuro; Ademodi, Bayo (Journal of the Japanese Association for Petroleum Technology, 2020)
Journal of the Japanese Association for Petroleum Technology vol. 38, no. 1, pg. 73-84